The Effect Of Information Quality, Customer Experience, Price, And Service Quality On Purchase Intention By Using Customer Perceived Value As Mediation Variables (Study On Gofood Applications On The Millenial Generation) - Orlando Gaberamos; Lamhot Henry Pasaribu (Jurnal Mantik, 2022)
This research was conducted with the aim of knowing the effect of information quality, customer experience, price and service quality on purchase intention by using a mediating variable, namely customer perceived value and knowing the partial relationship between the independent variable, the mediating variable and the dependent variable. The sample used is 100 respondents consisting of GoFood applications users in the millennial generation using non-probability sampling techniques. The data in this study came from a questionnaire with a Likert scale. Based on the results of data analysis, it shows that information quality has a positive effect on customer perceived value, customer experience has a positive effect on customer perceived value, price has a positive effect on customer perceived value and service quality has a positive effect on customer perceived value. In addition, customer perceived value has a positive influence on purchase intention. All relationships between variables have a positive influence and significant influence.